Malpractice claims related to diagnostic errors in the hospital. Issue 1 (9th August 2017) - Gupta, Ashwin; Snyder, Ashley; Kachalia, Allen; Flanders, Scott; Saint, Sanjay; Chopra, Vineet
Abstract : Background: Little is known about the incidence or significance of diagnostic error in the inpatient setting. We used a malpractice claims database to examine incidence, predictors and consequences of diagnosis-related paid malpractice claims in hospitalised patients. Methods: The US National Practitioner Database was used to identify paid malpractice claims occurring between 1 January 1999 and 31 December 2011. Patient and provider characteristics associated with paid claims were analysed using descriptive statistics. Differences between diagnosis-related paid claims and other paid claim types (eg, surgical, anaesthesia, medication) were assessed using Wilcoxon rank-sum and χ 2 tests. Multivariable logistic regression was used to identify patient and provider factors associated with diagnosis-related paid claims. Trends for incidence of diagnosis-related paid claims and median annual payment were assessed using the Cochran-Armitage and non-parametric trend test. Results: 13 682 of 62 966 paid malpractice claims (22%) were diagnosis-related. Compared with other paid claim types, characteristics significantly associated with diagnosis-related paid claims were as follows: male patients, patient aged > 50 years, provider aged <50 years and providers in the northeast region. Compared with other paid claim types, diagnosis-related paid claims were associated with 1.83 times more risk of disability (95% CI 1.75 to 1.91; p<0.001) and 2.33 times more risk of death (95% CI 2.23 to 2.43; p<0.001) than minor injury, after adjusting for patient and provider characteristics. Inpatient diagnostic error accounted for $5.7 billion in payments over the study period, and median diagnosis-related payments increased at a rate disproportionate to other types. Conclusion: Inpatient diagnosis-related malpractice payments are common and more often associated with disability and death than other claim types. Research focused on understanding and mitigating diagnostic errors in hospital settings is necessary.